An Efficient Two-Step Protocol for the Isoprenylation of Xanthone at the C2 Position Starting from 1-Fluoroxanthone Derivative - Fujimoto, Yuuki; Furukawa, Chisato; Takahashi, Kanae; Mochizuki, Miho; Yanai, Hikaru; Matsumoto, Takashi (Synlett, 2020)
The SNAr reaction of 1-fluoroxanthone derivatives with alkoxide of 1,1-dimethylallyl alcohol cleanly afforded the corresponding ethers, which have thus far been unavailable. The obtained ethers underwent the Claisen rearrangement at room temperature by treatment with silica gel in toluene. This two-step protocol provides expeditious and high-yield access to xanthones possessing isoprenyl or the related allylic side chain at the C2 position.
Keywords: xanthone; isoprenylation; SNAr reaction; Claisen rearrangement